Strain mapping in symmetrical core-shell gold nanorods from HRTEM images. (November 2021) - Zhang, Hui; Zhang, Ran; Geng, Yongfeng; Ji, Yinglu; Zhang, Yi; Li, Xu; Meng, Dejing
Abstract: Strain distribution, interface type and the causes of strain in gold core-shell nanorods were studied by employing high-resolution electron transmission microscope (HRTEM) and Geometric Phase Analysis (GPA). Anisotropic Strain distributions in gold core-shell nanorods were affected by l -cysteine (Cys) concentration and AA/Au 3+ ratio which determines shell growth kinetics. Strain circles were generated at the core-shell interfaces of gold nanorods. The {002} strain distributions of gold nanorods were very sensitive to the increase of Cys concentration and AA/Au 3+ ratio. Strain distributions with high strain values on {111} planes were more significant than that on {002} planes. This state was related to the preferential adsorption of thiols on {111} planes. The core-shell interface of gold nanorods was determined to be a mix of distorted coherent interface and semi-coherent interface, which was mainly produced via the slip of {111} planes along <110> slip direction. The gold shell covered the whole core at the growth conditions of different Cys concentrations and AA/Au 3+ ratios provided in this work via seed-mediated symmetric epitaxial growth. The strain at the core-shell interface was mainly generated by Au–S bonds and lattice distortion. Graphical abstract: Image 1 Hightlights: The strain of the core-shell gold nanorods was affected by l -Cysteine concentration and AA/Au 3+ ratio. {111} strain was more sensitive than {002} strain to the change of synthesis conditions. The gold nanorod core-shell interface was a mix of distorted coherent interface and semi-coherent interface. Shell growth was attributed to seed-mediated epitaxial growth with symmetry. Au–S bonds and lattice distortion were the main causes of strain at the core-shell interface.